Desafios do modelo de franquias no setor de perfumaria e cosméticos brasileiro, sob o ponto de vista de franqueados e franqueadores - Rodrigues, Claudia Regina (2010)
The objective of this study is to understand the challenges that could contribute for the franchising to become a representative distribution channel in the Brazilian cosmetic market. The research was conducted from a qualitative approach, in which were made twenty and two interviews with franchisors and franchisees, in the period between September and November of 2010. The interviewees were members of the following companies: Água de Cheiro, Antídoto, Contém 1g, Mahogany e O Boticário. The results were that the franchise model is seen by franchisees and franchisors as a good alternative for distribution and capillarity of the brand. However, the franchise model presents some challenges, such as the improvement of the franchisor´s engagement, a better selection process of franchisees, increase financial support, adjust the stores location method and, finally, improve the method for setting royalties.